Motivating people living with HIV to initiate antiretroviral treatment outside national guidelines in three clinics in the HPTN 071 (PopART) trial, South Africa. Issue 1 (2nd January 2021) - Mubekapi-Musadaidzwa, Constance; Wademan, Dillon; Peton, Neshaan; Hendricks, Portia; Carolus, Gabriela; Mbaezue, Rheiner; Kelley, Karen F; Kruger, James; Jennings, Karen; Grobbelaar, Nelis; Louis, Francoise; Beyers, Nulda; et al.
Abstract : Background : The HPTN 071 (PopART) trial implemented universal test and treat (UTT) in three clinics in the Western Cape, South Africa at a time when antiretroviral treatment (ART) was only offered by CD4 threshold and World Health Organization clinical staging. This required a concomitant shift in the way health workers communicated ART initiation messages. We provide insight into front-line ART initiation communication pre-national policy shift. Method : The design of this study was exploratory with a case descriptive analysis of ART initiation in three clinics. To characterise their demographic profiles, we reviewed 134 randomly selected patient clinical folders of people who initiated ART at CD4 counts greater than the recommended standard. Further, we conducted 12 key informant interviews with health workers at these facilities and thematically analysed health workers' responses. Results : The median age of patients initiating ART regardless of CD4 count (above the threshold level) was 33 years and most were women (73.9%), married (76.1%), and unemployed (48.5%). The median CD4 count of patients initiating outside guidelines was 566.5 cells/µl. Contrary to expectations, key informants indicated no radical shift in messaging to explain ART initiation regardless of CD4 count. Rather, they encouraged people living with HIV (PLHIV) to initiate ART while they still "feel well". The reduced risk of onward HIV transmission did not factor significantly in how health workers motivated clients. Conclusion : Motivating PLHIV to initiate ART regardless of CD4 count in high burden settings is possible. However, there are still opportunities to improve messaging about immediate ART initiation or at high CD4 counts for the prevention of onward transmission.